Phlebotomus (Adlerius) simici NITZULESCU, 1931: first record in Austria and phylogenetic relationship with other Adlerius species - Kniha, Edwin; Dvořák, Vít; Milchram, Markus; Obwaller, Adelheid G; Köhsler, Martina; Poeppl, Wolfgang; Antoniou, Maria; Chaskopoulou, Alexandra; Paronyan, Lusine; Stefanovski, Jovana; Mooseder, Gerhard; Volf, Petr; et al. (Parasites & vectors, 2021)
BACKGROUND: Phlebotomine sand flies are the principal vectors of Leishmania spp. (Kinetoplastida: Trypanosomatidae). Information on sand flies in Central Europe is scarce and, to date, in Austria, only Phlebotomus mascittii has been recorded. In 2018 and 2019, entomological surveys were conducted in Austria with the aim to further clarify sand fly distribution and species composition. RESULTS: In 2019, a Ph. simici specimen was trapped in Austria for the first time. Analyses of two commonly used marker genes, cytochrome c oxidase I (coxI) and cytochrome b (cytb), revealed high sequence identity with Ph. simici specimens from North Macedonia and Greece. Phylogenetic analyses showed high intraspecific distances within Ph. simici, thereby dividing this species into three lineages: one each from Europe, Turkey and Israel. Low interspecific distances between Ph. simici, Ph. brevis and an as yet unidentified Adlerius sp. from Turkey and Armenia highlight how challenging molecular identification within the Adlerius complex can be, even when standard marker genes are applied. CONCLUSION: To our knowledge, this study reports the first finding of Ph. simici in Austria, representing the northernmost recording of this species to date. Moreover, it reveals valuable insights into the phylogenetic relationships among species within the subgenus Adlerius. Phlebotomus simici is a suspected vector of L. infantum and therefore of medical and veterinary importance. Potential sand fly expansion in Central Europe due to climatic change and the increasing import of Leishmania-infected dogs from endemic areas support the need for further studies on sand fly distribution in Austria and Central Europe in general.
Keywords: Psychodidae; Austrálie; cytochromy b; Cytochromes b; Phlebotomus; Leishmaniasis, Visceral; fylogeneze; Phylogeny; Genes, Insect; klasifikace; Disease Vectors; leishmanióza viscerální; Classification; respirační komplex IV; hmyz - vektory; Refugial area; Electron Transport Complex IV; Animals; hmyzí geny; zvířata; Leishmania infantum; Phlebotomine sand fly; infekce přenášené vektorem; Insect Vectors; Central europe; Australia; Adlerius